Penerapan Sistem Tracking Berbasis GPS pada Alat Pendeteksi Alkohol Terintegrasi dengan Arduino untuk Pengemudi Mobil Penumpang Umum - Jusuf, Abd Karim; Agus, Muh (Universitas Pancasakti, 2023)
Regarding the problems faced by managers of the transportation business, namely cases of vehicle theft which still often occur, therefore an idea emerged on how owners can monitor their vehicles effectively, then accidents that usually occur due to reckless public transportation drivers due to influence of liquor. Based on the background described above, the authors aim to conduct research by creating a GPS tracking tool that is integrated with Arduino, which is able to monitor the location of the driver/vehicle and is able to reduce vehicle embezzlement, and the system to be designed is able to detect whether the driver of the vehicle is in a state of drink alcohol or not. Research has been carried out on 2 people, namely for the first person, the lowest sensor data reading was obtained, namely 22 ppm with a delay of 2 seconds for GPS readings for a distance of 3.5 km and the condition of the relay was off indicating that alcohol was not detected, and for the highest sensor data readings it was at 109 ppm with a delay of 3 seconds GPS reading for a distance of 4.2 km and the condition of the relay is on which indicates alcohol is detected. In the second person test, the lowest sensor data reading was obtained, namely 23 ppm with a 4 second GPS reading delay for a distance of 11 km and the condition of the relay was off indicating no alcohol was detected, and the highest sensor data reading was 121 ppm with a 2 second GPS reading delay for a distance 10 km and the condition of the relay is on which indicates alcohol is detected. GPS testing was carried out 10 times for each person where the longest distance tested on the first person was 42 km, and the shortest distance was 3.3 km. And for the test, the fastest delay in reading the driver's location is 2 seconds, and the longest is 5 seconds. In testing the second person, the longest distance was 12 km, and the shortest distance was 10 km. And in the test, the fastest delay in reading the driver's location point is 2 seconds, and the longest delay in reading the location point is 4 seconds.